Increasing of Early High-Risk Pregnancy Detection with Proactive Intervention in Bangkalan District, Madura Indonesi - Budi Prasetyo (Journal of Global Pharma Technology, 2020)
Background: Maternal Mortality Rate (MMR) in Indonesia remains high despite various initiatives had been done to decrease. Factors that correlate with it are culture and referral. In this study, a proactive intervention was conducted to improve cultural and referral issues in a rural area. Aim: to explain the improvement of the early detection of high-risk pregnancy after a proactive intervention. Method: This study is an experimental design by implemented proactive intervention complemented antenatal care programs in the primary health care center. Midwifery students were enlisted to conduct a maternal assistance program to raise awareness of the importance of antenatal care visits, childbirth by health workers, and family planning programs. Results: The proactive intervention showed the increasing of early detection of high-risk pregnancy by skilled health personnel (p =